The knowledge of public managers about water resources and environmental education in Palmeira das Missões/RS (Research, Society and Development, 2022)
The present work aimed to verify the knowledge of public managers in the municipality of Palmeira das Missões, Rio Grande do Sul, about the importance of water resources in their area of ​​operation. To this end, a questionnaire with open and closed questions was applied to a total of 20 managers representing different institutions in the municipality. A qualitative-quantitative, cross-sectional and exploratory research was conducted. For that, data was collected through a questionnaire applied to 20 managers working in the public administration of that municipality. Numerical data analysis was performed using the quantitative statistical analysis method using the STATA software version 12.1 and considering the value of 5% as a reference for statistical significance (p-value